2022
DOI: 10.1021/acscatal.2c03531
|View full text |Cite
|
Sign up to set email alerts
|

Ru(II)/Chiral Carboxylic Acid-Catalyzed Asymmetric [4 + 3] Annulation of Sulfoximines with α,β-Unsaturated Ketones

Abstract: Sulfur-stereogenic containing benzo-fused heterocycles have gained much attention in drug discovery. However, the asymmetric synthesis of these chiral molecules with structural diversity is very challenging. Herein, we report the synthesis of chiral benzothiadiazine-1oxides with a seven-membered ring via achiral Ru(II)-catalyzed asymmetric [4 + 3] annulation of sulfoximines with α,β-unsaturated ketones assisted by chiral carboxylic acid (CCA). A broad range of chiral benzothiadiazepine-1-oxides bearing various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Based on pervious work [6g–h,16a,c] and our mechanistic studies, we propose a plausible catalytic cycle as shown in Scheme 6. First, enantioselective C−H cleavage takes place through the enantiocontrol transition state TS B , whcih may be formed with the cooperation of the Rh(III) catalyst, sulfoximine 1 , and the spiro‐CCA L2 based on hydrogen bonding interaction, [6g] affording a chiral Rh(III) intermediate C .…”
Section: Resultsmentioning
confidence: 99%
“…Based on pervious work [6g–h,16a,c] and our mechanistic studies, we propose a plausible catalytic cycle as shown in Scheme 6. First, enantioselective C−H cleavage takes place through the enantiocontrol transition state TS B , whcih may be formed with the cooperation of the Rh(III) catalyst, sulfoximine 1 , and the spiro‐CCA L2 based on hydrogen bonding interaction, [6g] affording a chiral Rh(III) intermediate C .…”
Section: Resultsmentioning
confidence: 99%
“…For example, para -substituted diarylsulfoximines bearing electron-donating groups (OMe, Ph) often benefited to the dialkylation/cyclization products, and the para - or meta -substituted diarylsulfoximines sulfoximines with electron-withdrawing groups would help to access mono alkylation/cyclization products. Moreover, a series of chiral N-benzoyl sulfoximines with a C–S chiral axis could be obtained after the oxidative cleavage of the double bonds in the products ( Scheme 29 ) [ 45 ].…”
Section: Synthesis Of Cyclic Sulfoximines Via Intermolecular C–h Acti...mentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] NH-sulfoximines as an analogue of sulfones are widely present in many drug molecules, and they can be directly N-H functionalized to synthesize complicated scaffolds with potential applications. [17][18][19][20][21][22][23] In recent years, N-H arylation, alkylation (Scheme 1(Aa)), and removal of SQN-directed groups (Scheme 1(Ab)) of NHsulfoximines under electrochemical conditions have been reported successively. [24][25][26][27][28] For instance, in 2021, Mei's group first developed a Ni-catalyzed electrochemical N-arylation reaction of aryl halides and NH-sulfoximines.…”
Section: Introductionmentioning
confidence: 99%